2017
DOI: 10.1088/1361-6595/aa6426
|View full text |Cite|
|
Sign up to set email alerts
|

Dielectric barrier discharges: progress on plasma sources and on the understanding of regimes and single filaments

Abstract: Dielectric barrier discharges (DBDs) are plasmas generated in configurations with an insulating (dielectric) material between the electrodes which is responsible for a self-pulsing operation. DBDs are a typical example of nonthermal atmospheric or normal pressure gas discharges. Initially used for the generation of ozone, they have opened up many other fields of application. Therefore DBDs are a relevant tool in current plasma technology as well as an object for fundamental studies. Another motivation for furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
443
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(454 citation statements)
references
References 321 publications
9
443
0
2
Order By: Relevance
“…Gases such helium with admixtures of oxygen or air are usually used. For more information on the working of the DBD see references [61,78,79]. Figure 2 shows a schematic of the DBD and a photograph of a diffuse plasma at atmospheric pressure generated by a DBD.…”
Section: Two Ltp Sources For Biomedical Applications: Brief Descriptionmentioning
confidence: 99%
“…Gases such helium with admixtures of oxygen or air are usually used. For more information on the working of the DBD see references [61,78,79]. Figure 2 shows a schematic of the DBD and a photograph of a diffuse plasma at atmospheric pressure generated by a DBD.…”
Section: Two Ltp Sources For Biomedical Applications: Brief Descriptionmentioning
confidence: 99%
“…Dielectric barrier discharges (DBD) enable the generation of non‐thermal (low temperature) plasmas at atmospheric pressure . A dielectric material (e.g., glass, polymer, or ceramic) is typically placed between two electrodes, maintaining a small discharge gap of a few mm.…”
Section: Reactor Design Considerationsmentioning
confidence: 99%
“…For SBD both electrodes are in direct contact with the barrier with the plasma is formed in the gas at the exposed surface electrode. [37] Recent scale-up efforts at the University of Liverpool aimed directly at in-situ decontamination of food and foodprocessing equipment have been reported. [38] Bauer et al reported on the system's design features and its anti-microbial efficacy for treating food packaging films.…”
Section: Surface and Coplanar Dielectric Barrier Dischargesmentioning
confidence: 99%
“…For coplanar discharges both electrodes are embedded in the dielectric material with the discharge forming in the gas above the dielectric surface. [37] This design is -15 -particularly suited to food applications as the electrodes can be completely sealed off from any food/water contact. It is also compatible with scale-up.…”
Section: Surface and Coplanar Dielectric Barrier Dischargesmentioning
confidence: 99%